HUBUNGAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN MENULIS RESENSI SISWA KELAS XI SMA NEGERI I SOSOPAN. - bayo angin, toras barita (Institut Pendidikan Tapanuli Selatan, 2018)
abstrak   Reading is a process undertaken to obtain a message so that the message obtained can be received well, it is better to do the reading activity in the heart which is also called reading comprehension. Write a review is an activity to write book reviews or book scales. In order to write a book review done well then we first read the book to be diresensi it. To read the book is better implemented by reading comprehension activities. The purpose of this study is to describe the relationship of reading comprehension skills by writing a student review of grade XI SMA Negeri I Sosopan. The respondents of this research are students of class XI SMA Negeri I Sosopan which amounted to 30 people. The type of this research is descriptive by using quantitative approach. The data obtained from the analysis of test scores obtained by respondents who answered questions in the form of objective and subjective. The objective test consists of 50 questions. The subjective test data were obtained from the student data which made reviews of the two short stories that were shared. The collected data were analyzed by the following steps: 1) grouping the students scores per aspect and generally using the percentage formula, 2) grouping the student scores into a scale of 10, 3) finding the average test score of the students, 4) testing death correlation used the test formula